Beyond Dichotomous Approach, Experts Method Compatibles with an Information System View for Developing a Valid Corporate Governance Index - Maysa Ali Abdallah (Journal of Corporate Governance Research, 2024)
This paper provides a critical review of the corporate governance quantification process at academic and professional levels to scrutinize the main troubles in the black box of CG assessment models and spot some lights on how to develop a valid Corporate Governance Index (CGI) at the firm and industry levels regarding evenly the entire stakeholders' perceptions. Prior literature has been reviewed and a Corporate Governance index was constructed merging the power of multi-methodologies: Principal Component Analysis (PCA), Delphi Technique and Stability analysis. The findings show that the validity of the results necessitates enforcing End to End processes and taking into account the country's individualization to increase the reliability and comparability of the results. As well, the governance ratings are sensitive to the applied methodology, particularly, a well-known approach in quantifying CG, i.e., dichotomous approach, is underestimated the index findings then it will directly affect all aspects of governance endogeneity with firm’s performance/value. This research has important practical implications for governance guidelines setters, companies, stakeholders and other researchers. For the G setters, it underlines the necessity to make harmonization between industries' regulations and governance code, and revise the priority of the "comply or explain" approach in practice; which could serve as a roadmap for future improvements and researches. For companies, this paper highlights which effective G mechanisms and urges the role of the boardroom in monitoring and explanations for non-compliance. For CGI users, the research highlights that ratings' users should be more precautions and concerned about the base of the assessing models.